Two cSNPs sites in the fatty acid-binding protein 4 (FABP4) gene and their association analysis with body measurement data in five Chinese cattle breeds. Issue 7 (12th December 2022) - Xu, Jiawei; Liu, Xian; Cai, Cuicui; Su, Woyu; Xie, Jianliang; Zhang, Zijing; Yang, Peng; Lyu, Shijie; Li, Zhiming; Lei, Chuzhao; Chen, Hong; Wang, Eryao; et al.
Abstract: Single nucleotide polymorphisms (SNPs) include the transition and transversion of a single base. In this study, we found two cSNPs (rs110757796 and rs110652478) in the FABP4 (fatty acid-binding protein 4) gene and tested their population genetic parameters in five Chinese cattle breeds. FABP4 is a key marker molecule for lipid production. It plays a crucial role in the growth and development of animals. Thus, we also analyze the association between the two cSNPs of FABP4 gene and body measurement data of Chinese cattle. Our results were indicated that rs110757796 was significantly associated with the chest width in Chinese cattle groups ( p  < 0.05). In addition, we tested the spatiotemporal expression profile of the bovine FABP4 gene and effect of genetic variation on its expression. It was found that bovine FABP4 gene has tissue-differential expression. Then, the genetic variation located on the exon has a certain effect on the expression of FABP4 gene in bovine muscle. Overall, our results provide that FABP4 could as a candidate gene to improve the progress of cattle molecular breeding.